Are You doing the Right Things? Initial Stages of Individuals Change Management: Identify, Acknowledge and Make a Courageous Move Framework - Salmela, Erno; Happonen, Ari (Selected Topics in Humanities and Social Sciences Vol. 2, 2021)
In sports, too little attention has been paid concerning why changes are important for personal development and who exactly should notice when a change in personal activities would be needed. People themselves do not necessarily recognize that their efforts and goals are not in good sync. When this happens, they make changes to their routines, when things go badly wrong, but at the same time they can be blind for their inefficient ways of working. Authors have created a framework to ease the issue to identify a need for change to achieve sports goals. The research focused into the forefront of change management: Identifying and acknowledging need(s) for change, especially in initial stages of individuals change needs detection phase. As result, we propose Identify, acknowledge, and make a courageous move framework. With these stages, one can elicit appropriate changes. The value of the study lies in an overall and profound examination of the initial stages of sport training related change management.